Miniaturized dual-band bandpass filter with closely spaced passbands and wide stopband - Li, Yijun; Ni, Jinxuan; Li, Siyu; Han, Qian; Tian, Jie; Li, Na; Ma, Tianye (Frontiers in Physics, 2025)
This work presents a new miniaturized dual-band bandpass filter (BPF) featuring closely spaced passbands and wide stopband performance. The filter is designed on a slots-loaded substrate integrated waveguide (SIW) cavity fed by microstrip line. By introducing a longitudinal rectangular slot at the cavity’s center symmetry line and two transverse rectangular slots at the upper and lower edges, two shorted patches are formed within the SIW. A second-order BPF is constructed through the gap coupling. Subsequently, two quarter-wavelength resonators are introduced into the upper and lower transverse slots, which are respectively coupled with two shorted patches. This configuration allows the second-order filtering passband, formed by shorted patches coupling, to be split into two second-order closed passbands with frequency ratio of 1:1.04. Due to the low harmonic characteristics of the shorted patches, the designed dual-band BPF achieves a −20 dB stopband range of up to 2.86f0. Finally, a prototype is designed, fabricated, and measured to validate the proposed design, demonstrating good consistency between the simulated and measured results.